Socio-Economic Priorities State Budget Formation in the Long Term - A. A. Belostotskiy (Vestnik MGIMO-Universiteta)
In the research study analyzes the socioeconomic development, the role of the state budget in the financing of social activities at the federal and regional levels and the direction of the effective budget implementation in the long term